THE PROFIT OPPORTUNITIES ON THE INTERNET OF THINGS MARKET - A. Zubarev (Вестник университета)
The article examines current economic situation in the Internet of things, prospects and trends of its development. The possibilities of obtaining and ways to maximize profits by companies in this market are review. A simplified view of the value chain is presented. The possibilities of building business models are c considered. Shown the key groups of players, their role and potential influence in creating a value chain. The main risks associated with doing business in this market are given.